Шекспир сонетлерин қарақалпақ тилине аўдарыўдың айрым лексикалық ҳәм стилистикалық мәселелери ҳаққында - Турсынмуратова, З.М (SCIENCE and SOCIETY, 2023)
This article provides an analysis of the antonymy of comparative phraseological units of the English and Karakalpak languages. In this article, the problem of phraseological antonymy is singled out as a category opposite to phraseological synonymy and from a scientific point of view, is studied in close connection with it.
Keywords: рoetical translation; sonnet; parody; irony; lyricism; adequate translation